Producción de biomasa microalgal a partir de aguas residuales de la industria floricultora a nivel laboratorio (2018)
The wastewater from the floriculture industry, specifically from hydroponic crops, is a source that can be used for the growth of the Chlorella vulgaris microalgae, due to its nutrient content among other compounds that may contain these wastewater, which leads to This research will evaluate the growth of the microalga, with this source of nutrients for the production of microalgal biomass. The residual from the Las Acacias flowers farm, belonging to the Chía group, which allowed the sample to be taken from the Fredom rose cultivation. For the pre-experimental phase, three proportions of residual water / culture medium were selected as follows: (1: 1, 2: 1: 1: 2) The highest specific growth rate (μ) was selected, where it was obtained that for a 2: 1 ratio (200 mL residual water / 100 mL of culture medium) the specific growth rate is μ = 0.2745 dia-1 without ultraviolet radiation, and a specific growth rate of μ = 0.2921 dia-1 with ultraviolet radiation. In the experimental phase a biomass yield 39,12, an average growth rate of μ = 0,3698 (day -1) and a volumetric productivity of 0.0159 g / L * day of dry biomass were obtained for the experiment and an average growth rate of μ = 0.4095 dia-1, a volumetric productivity of 0.0241 g / L * day of dry biomass for the control.